Critical care, quick glance : - Maithel, Shishir Kumar. (McGraw-Hill Medical Pub. Division, 2006)
This concise, pocket sized guide to Critical Care medicine provides at-a-glance information for treating patients effectively and expiediently. Includes a free PDA download to facilitate its usefulness at the point of care.